Antioxidant Capacity, Enzyme Activities Related to Energy Metabolism, and Transcriptome Analysis of Crassostrea hongkongensis Exposed to Hypoxia - Pingping He; Wei Li; Pinyuan Wei; Linyuan Jiang; Junliang Guan; Yuan Ma; Li Zhang; Yongxian Chen; Yusi Zheng; Xingzhi Zhang; Jinxia Peng (MDPI AG, 2024)
Crassostrea hongkongensis (C. hongkongensis) is one of the three most commonly cultivated oyster species in China. Seasonal hypoxia is one of the most serious threats to its metabolism, reproductive behavior, and survival. To investigate the effects of hypoxia stress on the antioxidant capacity and energy metabolism of C. hongkongensis, the total antioxidant capacity (T-AOC), glycogen content, and enzyme activities (phosphofructokinase, PFK; pyruvate kinase, PK; phosphoenolpyruvate carboxykinase, PEPCK) of oysters were determined under normoxic (DO 6 ± 0.2 mg/L) and hypoxic (DO 1.5 mg/L) conditions at 0 h, 6 h, 48 h, and 72 h. We also determined the T-AOC, glycogen content, and enzyme activities of oysters under reoxygenation (recovered to normoxia for 24 h). To further examine the potential molecular regulatory mechanism of hypoxic adaptation, a transcriptome analysis was conducted on the gill of C. hongkongensis under normoxia (N, 72 h), hypoxia (H, 72 h), and reoxygenation (R). After being exposed to hypoxia for 6 h, the T-AOC, glycogen content, and enzyme activities of PK, PFK, and PEPCK in C. hongkongensis were significantly decreased. However, after prolonging the duration of hypoxia exposure for 72 h, the T-AOC, glycogen content, and enzyme activities increased compared to that of 48 h. After 24 h reoxygenation, the T-AOC, glycogen content, and enzyme activity of PK and PFK returned to close to initial levels. In addition, a transcriptome analysis discovered 6097 novel genes by mapping the C. hongkongensis genome with the clean reads. In total, 352 differentially expressed genes (DEGs) were identified in the H vs. N comparison group (235 upregulated and 117 downregulated genes). After recovery to normoxia, 292 DEGs (134 upregulated and 158 downregulated genes) were identified in the R vs. N comparison group, and 632 DEGs were identified (253 upregulated and 379 downregulated genes) in the R vs. H comparison group. The DEGs included some hypoxia-tolerant genes, such as phosphoenolpyruvate carboxykinase (PEPCK), mitochondrial (AOX), tyramine beta-hydroxylase (TBH), superoxide dismutase (SOD), glutathione S-transferase (GST), and egl nine homolog 1 isoform X2 (EGLN1). Additionally, DEGs were significantly enriched in the KEGG pathways that are involved in hypoxia tolerance, including the metabolism of xenobiotics by cytochrome P450 pathways and the HIF-1 signaling pathway. Then, we selected the five hypoxic-tolerant candidate DEGs for real-time quantitative polymerase chain reaction (RT-qPCR) validation, and the results were consistent with the transcriptome sequencing data. These discoveries have increased our understanding of hypoxia tolerance, recovery ability after reoxygenation, and molecular mechanisms governing the responses to hypoxia in C. hongkongensis.